FACILITATING AUTOMATIC EXCHANGE OF INFORMATION ON BLOCKCHAIN: A SOUTH AFRICAN PERSPECTIVE - Ruddy Kabwe; Princess Thembelihle Ncube (Obiter, 2024)
Exchange of information is a mechanism that enables tax authorities to share tax information across borders. Exchange of information curtails harmful practices such as tax evasion and tax avoidance by promoting cooperation between tax authorities. Recent world events have seen unprecedented levels of globalisation and novel income-earning structures. Taxpayers earn income from streams that were previously unavailable. These developments have led tax authorities to implement policies that focus on improved financial transparency and better multilateral cooperation. This article argues for the implementation of blockchain technology to facilitate exchange of information in South Africa. Blockchain is a ledger that records and stores information on an online network. Blockchain’s features make it conducive for use in cross-border administration and exchange of tax information. Blockchain creates a platform for financial transparency because data stored on the blockchain is reliable and accurate. Tax information is exchanged in real time, thereby reducing tax authorities’ administrative burden and enhancing cooperation.